IgG anti-GQ1b positive acute ataxia without ophthalmoplegia. Issue 5 (1st November 1999) - Mori, Masahiro; Kuwabara, Satoshi; Koga, Michiaki; Asahina, Mayumi; Ogawara, Kazue; Hattori, Takamichi; Yuki, Nobuhiro
Abstract : IgG anti-GQ1b antibody was present in a patient with acute ataxia and areflexia without ophthalmoplegia or elementary sensory loss. Sensory nerve conduction studies and somatosensory evoked potentials were normal, but postural body sway analysis showed dysfunction of the proprioceptive afferent system. The clinical presentation and laboratory results for this patient resemble those of Miller Fisher syndrome, except for the lack of ophthalmoplegia. This case may represent part of an IgG anti-GQ1b syndrome.